HomeoboxC6 affects the apoptosis of human vascular endothelial cells and is involved in atherosclerosis. Issue 3 (1st August 2020) - Long, Xiangshu; You, Ganhua; Wu, Qiang; Zhou, Yu; Xiao, Yan; Yu, Fuxun; Deng, Shiyan; Mo, Rui; Song, Fang; Huang, Jing; Tian, Maobo
Abstract: Apoptosis of vascular endothelial cells (VECs) is highly important in the occurrence and development of atherosclerosis (AS). HomeboxC6 (HOXC6) is expressed in higher levels in multiple malignant tissues, and it influences the malignant biological behavior of the cancer cells. However, the effects of HOXC6 on AS and the apoptosis of VECs have not been fully elucidated. In this study, we demonstrated that HOXC6 expression was increased in aortic wall of AS rats and peripheral blood monocytes of patients with coronary heart disease. Furthermore, it was uncovered that BAX expression was upregulated, while BCL‐2 expression was downregulated in the aortic wall of AS rats. The apoptosis of human VECs (HVECs) cultured normally or treated with oxidized low‐density lipoprotein in vitro was decreased after transfection with HOXC6 ‐siRNA. Moreover, the results of Western blot analysis unveiled that the expressions of proapoptotic proteins, such as BAX, caspase‐3, cleaved‐caspase‐3, and caspase‐9 were reduced, while the expression of antiapoptotic protein, BCL‐2, was elevated. Meanwhile, mRNA and protein expressions of phospholipase C beta (PLCβ) were decreased, the phosphorylation levels of protein kinase C zeta (PKCζ) and nuclear transcription factor‐κB‐p65 (NF‐κBp65) and the membrane translocation of PKCζ were reduced as well. Besides, the expression of interleukin‐18 (IL‐18) protein was downregulated. However, after overexpression of HOXC6, the opposite trends of the abovementioned indices were observed. Furthermore, the inhibition of apoptosis induced by HOXC6 ‐siRNA was reversed by lysophosphatidylcholine, an activator of PKCζ. Taken together, our results indicated that HOXC6 can promote the apoptosis of HVECs and may be involved in the occurrence and development of AS, which may be partially associated with the activation of PLCβ/PKCζ/NF‐κBp65/IL‐18 signaling pathway. Abstract : HOXC6 can induce the apoptosis of HVECs, which can be partially related to the activation of PLCβ/PKCζ/NF‐κBp65/IL‐18 signaling pathway by HOXC6. HOXC6 may be involved in the occurrence of AS by promoting the apoptosis of HVECs, and downregulating HOXC6 expression in the vascular wall may play a role in inhibiting the progression of AS.